Current Status of 3-Dimensional Speckle Tracking Echocardiography: A Review from Our Experiences - Seo, Yoshihiro (Korean Society of Echocardiography, 2014)
Cardiac function analysis is the main focus of echocardiography. Left ventricular ejection fraction (LVEF) has been the clinical standard, however, LVEF is not enough to investigate myocardial function. For the last decade, speckle tracking echocardiography (STE) has been the novel clinical tool for regional and global myocardial function analysis. However, 2-dimensional imaging methods have limitations in assessing 3-dimensional (3D) cardiac motion. In contrast, 3D echocardiography also has been widely used, in particular, to measure LV volume measurements and assess valvular diseases. Joining the technology bandwagon, 3D-STE was introduced in 2008. Experimental studies and clinical investigations revealed the reliability and feasibility of 3D-STE-derived data. In addition, 3D-STE provides a novel deformation parameter, area change ratio, which have the potential for more accurate assessment of overall and regional myocardial function. In this review, we introduced the features of the methodology, validation, and clinical application of 3D-STE based on our experiences for 7 years.